Multi-Term Asymptotic Representations of the Riesz Measure of Subharmonic Functions in the Plane - Agranovich, P. (Журнал математичної фізики, аналізу, геометрії, 2009)
In the paper, a multi-term asymptotic representation for distributionfunction of the Riesz measure of subharmonic function in the plane is considered. It is shown that the "smallness" of the reminder term of asymptotic representation does not guarantee the bounded variation with respect to the angle variable of all terms of this asymptotics, and the conditions for this property to be held are given. Mathematics Subject Classification: 31A05, 31A10, 26A45.